The Intrinsic Logic of Industrial Internet Driving the Digital Transformation of SMEs and Policy Recommendations - Cao, Huashen (International Journal of Social Sciences and Public Administration, 2024)
The industrial internet, as a deep integration of new-generation information and communication technologies with the industrial economy, provides an accelerator for the digital transformation of small and medium-sized enterprises (SMEs). By connecting people, machines, objects, and systems, it constructs a new type of manufacturing and service system that encompasses the entire industrial chain and value chain, promoting the transformation and upgrading of the manufacturing industry. SMEs face challenges in digital transformation, such as insufficient digital knowledge reserves among management and employees, unclear transformation paths, and a lack of support for key elements. The intrinsic logic of the industrial internet lies in improving production efficiency and reducing costs, promoting innovation and business model transformation, and strengthening supply chain collaboration. Policy recommendations include enhancing the guidance of enterprise transformation capabilities, improving the supply level of transformation, and increasing policy support for transformation, to promote the digital transformation and high-quality development of SMEs.